Temperature induced phase transition from cycloidal to collinear antiferromagnetism in multiferroic Bi0.9Sm0.1FeO3 driven by f-d induced magnetic anisotropy: Data archive - Johnson, R; Khalyavin, D; Manuel, P; Knee, C; Svedlindh, P (University of Oxford, 2017)
Neutron powder diffraction data were collected on the WISH instrument at ISIS, the UK Neutron and Muon Spallation source. Magnetometry data were collected using a Quantum Design Magnetic Properties Measurement System, and heat capacity data were collected using a Quantum Design Physical Properties Measurement System.